2022
DOI: 10.1155/2022/9911472
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Bioinformatics Analysis of tRF/tiRNA in Endometriosis Patients

Abstract: Background. Endometriosis (EMs) is a benign chronic condition that tends to recur in women of childbearing age, with an incidence of approximately 10%. It is a multifactorial disease for which the pathogenesis is currently unclear. This study is aimed at investigating the expression and clinical significance of tRNA-derived small RNA (tsRNA), a novel noncoding small RNA with potential regulatory functions, in endometriosis. Methods. The tRF/tiRNA expression profiles in endometrial tissues from three pairs of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Many tiRNAs and tRFs are differentially expressed in response to stress, with most data coming from the realm of cancer biology [ 60 ]. tiRNAs and tRFs are also found to be differentially expressed in other diseases/conditions, including diabetic retinopathy [ 61 ], endometriosis [ 25 ], spinal cord injury [ 62 ], and many more. Some are involved in multiple pathologies—5′tiRNA-His-GTG was shown to respond to tissue hypoxia and may be involved in malignancy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many tiRNAs and tRFs are differentially expressed in response to stress, with most data coming from the realm of cancer biology [ 60 ]. tiRNAs and tRFs are also found to be differentially expressed in other diseases/conditions, including diabetic retinopathy [ 61 ], endometriosis [ 25 ], spinal cord injury [ 62 ], and many more. Some are involved in multiple pathologies—5′tiRNA-His-GTG was shown to respond to tissue hypoxia and may be involved in malignancy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pathology, tRFs were found to be differentially expressed in various cancers [ 21 ] and amyotrophic lateral sclerosis [ 22 ]. Various tiRNAs were even proposed to be hallmarks of various diseases [ 23 , 24 , 25 ] and as therapy options; in the latter, specific tRFs derived from exosomes were shown to alleviate systemic lupus erythematosus [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…And in vitro and in vivo experiments have found that RAP1 acts on the AKT signaling pathway to promote the growth of trophoblast cells, [41] ensuring that the early embryo receives sufficient trophoblast. In addition, clinical and laboratory experiments [42,43] have found that the levels of RAP1 and EPAC1 are higher in ectopic endometrium than in normal endometrium and they are positively correlated. It is speculated that RAP1 and EPAC1 may play a synergistic role in promoting the formation of new microvessels in endometrium and the proliferation and adhesion of endometrial cells, which are beneficial to embryo implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of tsRNA action is yet to be elucidated, recent evidence suggests a miRNA-like mode of action, and bioinformatic prediction of tsRNA (whether tRF or tiRNA) will still use similar miRNAs for prediction in some studies [46][47][48][49][50] . miRNAs can recognise their mRNA targets using their seed sequence (positions 2-7nt at their 5 ends) and suppress global mRNA translational activities.…”
Section: Prediction Of Target Genes Of Differentially Expressed Tsrnasmentioning
confidence: 99%